Patient attitudes towards electronics usage in a hospital-based orthopaedic clinic: a survey study. Issue 1 (January 2019) - McDaniel, Claire; Davis, Meghan; Kessler, Michael
Abstract : Background: Patients and physicians are increasingly using technology to deliver healthcare for both preserving information and communication methods. However, little research has been done into patient attitudes towards technology use in the outpatient orthopaedic clinic. Methods: A paper survey was conducted of 1000 patients in a mixed-specialty hospital-based orthopaedic surgery clinic to determine patient attitudes towards common technologies. Data analysis was performed using chi-squared and Fisher exact tests. Continuous variables were examined using Kruskal-Wallis tests. Results: Most patients reported approving of desktops (98.0%, 95% CI 96.9%-98.8%) or tablets (97.4%, 95% CI 96.2-98.3%) to access medical files, as well as communication methods such as cellular phones set to silent (92.1%, 95% CI 90.3%-93.7%) and pagers set to silent (94.3%, 95% CI 92.7%-95.6%). However, most patients disapproved of cellular phones set to ring (32.3%, 95% CI 29.4%-35.3%), and approved less of pagers that are set to beep mode (70.2%, 95% CI 67.3%-73.0%), indicating that patients dislike intrusions into the clinical encounter. Conclusions: The majority of patients approve of certain technology use in the outpatient orthopaedic clinic, specifically means to access medical records and nonintrusive communication methods. As patients rank the orthopaedic surgeons' bedside manner as a highly important aspect of outpatient clinical care, technology integration must be carefully done to preserve bedside manner.